Characterizing Dust‐Radiation Feedback and Refining the Horizontal Resolution of the MarsWRF Model Down to 0.5 Degree. Issue 3 (16th March 2021) - Gebhardt, C.; Abuelgasim, A.; Fonseca, R. M.; Martín‐Torres, J.; Zorzano, M.‐P.
Abstract: In this study, three simulations by the Mars Weather Research and Forecasting Model are compared: two 10 Martian year (MY) 2° × 2° simulations with (i) fully radiatively active dust and (ii) a prescribed dust scenario, and a (iii) 1 MY 0.5° × 0.5° simulation with prescribed dust as in (ii). From comparing (i) and (ii), we found that the impact of dust‐radiation feedback is individually different for any region. The most striking evidence are major dust lifting activities to the south of Chryse Planitia (S‐CP) seen in (i) but not in (ii). By contrast, dust lifting and deposition on the southern slopes and inside the Hellas Basin are similar in both simulations. The latter, in turn, points toward a similar near‐surface atmospheric circulation. In (iii), the total global amount of wind stress lifted dust is by a factor of ∼8 higher than in (ii), with S‐CP being a major lifting region as in (i). Nonetheless, the surface dust lifting by wind stress in (iii) may be also reduced regionally, as seen at the peak of Elysium Mons because of its unique topography. The zonal mean circulation in (i) is generally of a comparable strength to that in (ii), with exceptions in global dust storm years, when it is clearly stronger in (i), in line with a dustier atmosphere. The differences in the zonal mean circulation between (ii) and (iii) are mostly at lower altitudes and may arise because of differences in the representation of the topography. Plain Language Summary: In the Mars atmosphere, the combination of airborne dust and radiation has multiplying effects, which are termed "positive feedbacks." For instance, dust storms intensify when exposed to sun light: temperature differences between warm and cold air are enhanced and winds become stronger, that is, positive feedback. We run a Mars General Circulation Model, or more precisely, the Mars Weather Research and Forecasting Model, with and without such feedbacks. In addition, we refine the spatial resolution of the model from 2° to 0.5° latitude and longitude. Overall, we quantify the impact of feedbacks and spatial resolution on the outcome of model simulations. For that, we compare patterns of dust exchange between the surface and atmosphere between different model simulations. We find that the strength of the positive feedbacks may change considerably from place to place. For the 0.5° resolution, winds are planet wide much more effective in eroding surface dust, including an exception governed by the unique local topography at the Elysium Mons volcano. Key Points: Three MarsWRF model simulations, which differ in the treatment of dust and/or spatial resolution, are compared Dust‐radiation feedback is studied by comparing surface dust lifting between simulations with interactive and prescribed dust treatment The highest resolution simulation has increased surface dust lifting by the wind stress globally, but it may be also reduced locally